Ebola virus VP35 has novel NTPase and helicase-like activities. Issue 11 (8th May 2019) - Shu, Ting; Gan, Tianyu; Bai, Peng; Wang, Xiaotong; Qian, Qi; Zhou, Hui; Cheng, Qi; Qiu, Yang; Yin, Lei; Zhong, Jin; Zhou, Xi
Abstract: Ebola virus (EBOV) is a non-segmented, negative-sense RNA virus (NNSV) in the family Filoviridae, and is recognized as one of the most lethal pathogens in the planet. For RNA viruses, cellular or virus-encoded RNA helicases play pivotal roles in viral life cycles by remodelling viral RNA structures and/or unwinding viral dsRNA produced during replication. However, no helicase or helicase-like activity has ever been found to associate with any NNSV-encoded proteins, and it is unknown whether the replication of NNSVs requires the participation of any viral or cellular helicase. Here, we show that despite of containing no conserved NTPase/helicase motifs, EBOV VP35 possesses the NTPase and helicase-like activities that can hydrolyse all types of NTPs and unwind RNA helices in an NTP-dependent manner, respectively. Moreover, guanidine hydrochloride, an FDA-approved compound and inhibitor of certain viral helicases, inhibited the NTPase and helicase-like activities of VP35 as well as the replication/transcription of an EBOV minigenome replicon in cells, highlighting the importance of VP35 helicase-like activity during EBOV life cycle. Together, our findings provide the first demonstration of the NTPase/helicase-like activity encoded by EBOV, and would foster our understanding of EBOV and NNSVs.